Factors affecting employees' job satisfaction in WFH arrangement during COVID-19 a case study of private sectors in Leyte - Josol, Sandra Angelica Elli; Lelis, Ma. Krystal-Joy P.; Mantua, Charlene Joy P. (2022)
The primary purpose of this study was to find out what factors influenced private-sector employees' job satisfaction in WFH arrangements during the COVID-19 pandemic in Leyte. Using a sequential explanatory design, the study was able to determine employee motivation, challenges, and opportunities, as well as the various strategies that private sector and employees used during the WFH arrangement during COVID-19. The online survey questionnaire reached 71 respondents who met the researchers' criteria through snowball sampling. The findings revealed that the aspects of work that changed most when working from home include location, workload and stress level, and working hours. Furthermore, the findings also show that the employees' working environment, employment/work interruptions, and technical-related issues were among the factors influencing the decline in employee job satisfaction in the new normal arrangement during COVID-19. Aside from the previously mentioned factors, employees encountered opportunities in terms of creating social interactions at work, health and safety throughout the transition to WFH, and considerable changes in financial expenses during work-from-home arrangements. Furthermore, employees encouraged their companies to implement suggestions such as raises in salary, more benefits, and emotional and moral support from their employers. Employees should also (1) establish a solid balance between work and life; (2) refocus their goals; and (3) socialize, communicate, and collaborate, as all of these factors lead to increased job satisfaction.